Associations of community programs and policies with children's dietary intakes: the Healthy Communities Study. (10th July 2018) - Ritchie, L. D.; Woodward‐Lopez, G.; Au, L. E.; Loria, C. M.; Collie‐Akers, V.; Wilson, D. K.; Frongillo, E. A.; Strauss, W. J.; Landgraf, A. J.; Nagaraja, J.; Sagatov, R. D. F.; Nicastro, H. L.; et al.
Summary: Background: The impact of community‐based obesity prevention efforts on child nutrition has not been adequately studied. Objective: Examine relationships between number, type and intensity of community programs and policies (CPPs) and child nutrition. Methods: An observational study of 5138 children (grades K–8) in 130 U.S. communities was conducted in 2013–2015. CPPs were identified by 10–14 key informant interviews per community. CPPs were characterized based on: count, intensity, number of different strategies used and number of different behaviours targeted. Scores for the prior 6 years were calculated separately for CPPs that addressed primarily nutrition, primarily physical activity (PA) or total combined. Child intakes were calculated from a dietary screener and dietary behaviours were based on survey responses. Multi‐level statistical models assessed associations between CPP indices and nutrition measures, adjusting for child and community‐level covariates. Results: Implementing more types of strategies across all CPPs was related to lower intakes of total added sugar (when CPPs addressed primarily PA), sugar‐sweetened beverages (for nutrition and PA CPPs) and energy‐dense foods of minimal nutritional value (for total CPPs). Addressing more behaviours was related to higher intakes of fruit and vegetables (for nutrition and total CPPs) and fibre (total CPPs). Higher count and intensity (PA and total CPPs) were related to more consumption of lower fat compared with higher fat milk. A higher count (PA CPPs) was related to fewer energy‐dense foods and whole grains. No other relationships were significant at P  < 0.05. Conclusion: Multiple characteristics of CPPs to prevent obesity appear important to improve children's diets. Abstract : What is already known about this subject? Multi‐component and multi‐sector community interventions are recommended to prevent child obesity. Little is known about whether community programs and policies implemented in the U.S. are improving child nutrition; a better understanding of these efforts and their relationship to child nutrition can help inform community efforts. What this study adds? We conducted an observational study collecting dietary data from over 5000 children ages 4–15 years and retrospective data on community programs and policies in a diverse sample of 130 communities across the U.S. Different features of community policies and programs were related to better child nutrition – there is likely no 'single' or 'simple' solution. Policy and food environments that support children''s healthy food choices in conjunction with delivering information and enhancing skills are associated with better diets. It is important to target changes in multiple dietary behaviours – not only increasing healthy foods and beverages, but also limiting less healthy ones. This article is part of the supplement: The Healthy Communities Study: Examining Community Programs, Policies and Other Characteristics in Relation to Child Weight, Diet, and Physical Activity